A celiac case mimicking mitochondrial neurogastrointestinal encephalomyopathy (MNGIE) - Aksoy, Erhan; Tıraş-Teber, Serap; Deda, Gülhis (The Turkish Journal of Pediatrics, 2016)
Celiac disease (CD) is a chronic disease involving a number of systems in addition to gastrointestinal tract. Although not clear, it has been supposed that the neurological symptoms of CD develop due to immune-mediated mechanisms. In this paper, we present a rare case diagnosed with CD at 12 years of age, and presented with a clinical picture resembling mitochondrial neurogastrointestinal encephalomyopathy (MNGIE). She had onset of her neurological symptoms at the age of 6 years, they progressed despite various therapies, and she became wheelchair-bound.